An Extensible Monitoring and Adaptation Framework - CLARKE, SIOBHAN; STAIKOPOULOS, ATHANASIOS; POPESCU, RAZVAN (My University, 2009)
Several techniques have been defined for the monitoring and adaptation of applications. However, such techniques usually work in isolation and cannot be easily integrated to tackle complex monitoring and adaptation scenarios. Furthermore, applications may have special requirements which make it difficult to reuse such off-the-shelf approaches. In particular, these requirements may cross several application layers such as { the organisation of stakeholder roles, coordination of planned activities, and integration with third-party services. In this paper we outline a lightweight, loosely-coupled and extensible monitoring and adaptation framework that allows application developers to integrate monitoring and adaptation techniques as units that can be linked to solve complex requirements and achieve cross-layer adaptation. In order to cater for application-tailored adaptation units, we propose a pattern-based technique for the development and integration of adaptation units.
2nd Workshop on Monitoring, Adaptation and Beyond (MONA+) at iCSOC/ServiceWave Conference
PRESENTED
Keywords: Computer Science